2013
DOI: 10.1039/c3sm52090k
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of colloidal gels at intermediate volume fraction under start-up of shear flow

Abstract: The microstructural evolution of the colloidal gel at intermediate volume fraction (15%) under start-up of shear flow has been studied by using the Brownian dynamics simulation method. The structural change was analyzed from three points of view, on cluster length scale, on local length scale and on anisotropy.Correlating the stress change which showed stress overshoot with the structural change on the cluster length scale, a mismatch between the initiation of the structural rupture and the stress maximum was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 50 publications
3
55
0
Order By: Relevance
“…The conductance of the polymer network along the x axis is computed by drawing conceptual parallels with the resistance model of a typical electrical network 42 , in which one bridge possesses a conductance of 1 (that is, the no bridge case possesses zero conductance) and a voltage of 1 is applied between the left and the right boundaries. A similar study was reported recently on the structural network evolution of colloidal gels under shear flow using Brownian dynamics simulations 43 .…”
Section: Methodssupporting
confidence: 64%
“…The conductance of the polymer network along the x axis is computed by drawing conceptual parallels with the resistance model of a typical electrical network 42 , in which one bridge possesses a conductance of 1 (that is, the no bridge case possesses zero conductance) and a voltage of 1 is applied between the left and the right boundaries. A similar study was reported recently on the structural network evolution of colloidal gels under shear flow using Brownian dynamics simulations 43 .…”
Section: Methodssupporting
confidence: 64%
“…4b) as a function of preshear strain amplitude, detected in experiments. Secondly, as has been seen in other studies 16,59 , BD simulations can not accurately produce, at such intermediate and low particle volume fractions the two step yielding that is widely seen in experiments. For the latter, since hydrodynamic interactions are absent in Brownian Dynamics simulations, they become the obvious possible origin for such deviations.…”
Section: Discrepancies Between Experiments and Bd Simulationsmentioning
confidence: 71%
“…Core potential for particle-particle interaction was represented by a parabolic curve with a steep slope [21].…”
Section: Particle-particle Interactionmentioning
confidence: 99%
“…A stable region was assigned to describe a weakly aggregating particle [21]. To capture the nature of the aggregating particles, severe variations of the DLVO potential near the primary minimum were neglected and the stable region was assigned where no attractive force was assumed.…”
Section: Particle-particle Interactionmentioning
confidence: 99%